Open Education Week in the USARB Scientific Library, 2017 March (Confluenţe Bibliologice, 2017)
Is presented the report of the librarians activities of the USARB Science Library during the Open Education Week. During this week, were promoted meetings with students from different faculties, were presented book exhibitions from the SL USARB collection, both traditional and online.
Keywords: Open Education Week; book club